Fabrication and Characterization of MWCNTs Decorated ZnO Nanograins Based Sensor for Enhanced Performance Toward CO2 Gas - Mikayel Aleksanyan; Artak Sayunts; Gevorg Shahkhatuni; Zarine Simonyan; Davit Kananov; Rima Papovyan; Dušan Kopecký (Advanced Materials Interfaces)
Abstract In this study, a zinc oxide sputtering target is synthesized and nanostructured ZnO film is obtained using simple solid‐state reaction and RF (radio frequency) magnetron sputtering methods, respectively. The surface of the ZnO film is functionalized by saturating it with MWCNTs (multi‐walled carbon nanotubes) using the electron‐beam deposition method to produce a high‐performance CO2 sensor. The obtained CO2‐sensitive material is subjected to multifaceted structural, morphological, crystallographic, and elemental studies using a film thickness measurement profiler as well as scanning electron (SEM), transmission electron (TEM) microscopies, and energy dispersive X‐ray (EDX), X‐ray photoelectron (XPS), and Fourier transform infrared (FTIR) spectroscopies. The CO2 sensing characteristics of the ZnO/MWCNTs nanostructured resistive sensor designed onto the multi‐sensor platform are carefully studied in the temperature range of 25–250 °C with and without UV (ultraviolet) irradiation. The temperature of 150 °C without UV irradiation is confirmed as the preferable operating point where the response values are swiped from 2.5 to 5.7 corresponding to the CO2 concentration range of 100–5000 ppm, respectively, with the reproducible appearance of the real‐time curves. The high performance of the ZnO/MWCNT sensor makes it a likely candidate for successful incorporation into CO2 detectors.